Subregional pedoclimatic conditions with contrasted UV-radiation shape host-microbiome and metabolome phenotypes in the grape berry - Viviana Martins; Cécile Abdallah; António Teixeira; Carolina Moreira; Márcio Nóbrega; Arnaud Lanoue; Hernâni Gerós (Food Chemistry: X)
This study used integrative omics to address the response of key elements of the grapevine holobiont to contrasted pedoclimatic conditions found in distinct subregions of Douro Valley (Portugal). A metabolic OPLS-DA model predicted with 100 % accuracy the geographic origin of berries; higher UV radiation, higher temperature and lower precipitation stimulated the accumulation of phenolic acids, flavonols and malvidin conjugates, in detriment of amino acids, organic acids, flavan-3-ols, proanthocyanidins and non-malvidin anthocyanins. Metabarcoding showed a trade-off between bacteria and fungal diversity among subregions, with Pseudomonas, Lactobacillus, Aspergillus and Penicillium acting as intraregional microbial markers. The high phenotypic plasticity of berries and the role of microbes in this process are relevant upon current projections for increased UV radiation and temperature in Southern European viticulture, in a climate change scenario, with predicted impacts on regional wine quality and on the development of adaptation strategies for resilient viticulture.